Management of Cardiac Arrhythmias - Yan, Gan-Xin.; Kowey, Peter R.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2011)
Few areas of medicine are evolving as rapidly as cardiac electrophysiology. What were only a short time ago seen to be lethal rhythm disturbances can now be treated with confidence in a diverse spectrum of patients. The first edition of Management of Cardiac Arrhythmias, published over ten years ago, has served clinicians not only as a practical guide to cardiac arrhythmias, but also as a comprehensive reference source. The second edition builds upon the concise style and expert authorship of its predecessor to provide the most up-to-date information on the diagnosis and treatment of this group of diseases. The introductory chapters begin with historical perspectives of the field and move on to discuss the scientific basis of arrhythmogenesis and diagnostic testing. The book then devotes specific chapters to various arrhythmias, including technical innovations in treatment and insights from clinical trials of and current guidelines for permanent pacemakers and implantable cardioverter-defibrillators. Subsequent chapters focus on arrhythmias in specific populations, including athletes, children, and women during pregnancy. Syndromes such as syncope, long and short QT syndrome, and J wave syndromes are also covered. Presenting complex information in a clearly structured and efficient format, this book is an incomparable asset to cardiologists and other physicians and health care professionals involved in the treatment of patients with cardiac arrhythmias.
Historic Perspective -- Mechanisms of Arrhythmogenesis -- Genetic and Molecular Basis of Arrhytmias -- Diagnosis and Molecular Basis of Arrhytmias -- Diagnosis of Arrhytmias with Non-invasive Tools -- Electrophysiological Study: Indications and Interpretaions -- Supraventricular Tachycardias -- Pharmacologic Management of Atrial Fibrillation and Flutter -- Catheter Ablation of Atrial Fibrillation and Flutter -- Nonsustained Ventricular Tachycardias -- Ventricualr Tachycardias and Fibrillation: Pharmacological Therapy -- Catheter Ablation of Ventricular Tachycardias -- Indications for Implantable Cardioverter Defibrillators -- Bradyarrhythmias -- Arrhytmias in Athletes -- Arrhytmias during Pregnancy and Postpardum -- Arrhytmias in Children -- Syncope -- Long QT Syndrome -- Short QT Syndrome -- J wave Syndromes -- The Last Word.
Keywords: Medicine; Internal medicine; Cardiology; Medicine & Public Health; Cardiology; Internal Medicine